Peran Agroindustri Hulu dan Hilir Dalam Perekonomian dan Distribusi Pendapatan di Indonesia - Nandika Aisya Pratiwi; Harianto Harianto; Arief Daryanto (School of Business, Bogor Agricultural University (SB-IPB), 2017)
This study aims to analyze the comparison of roles of the upstream and downstream agroindustries on the economy and income distribution of the Indonesian people. The analyzed economic indicators include output, employment, GDP, exports and imports. The data used in this study were from the Data of Social Accounting Matrix (SAM) as the latest data issued by Central Bureau of Statistics in 2008. The roles of upstream and downstream agroindustries were analyzed using accounting multiplier analysis. In the national economy, downstream agroindustry is more instrumental in the creation of output, added value, and imports while upstream agroindustry has a bigger role in the creation of GDP and exports. In terms of people's income distribution, downstream agroindustry creates a more equitable distribution of income both for domestic agriculture and non-agriculture.Keywords: agroindustry, GDP, income distribution, SAMABSTRAKPenelitian ini bertujuan menganalisis perbandingan peran agroindustri hulu dan hilir terhadap perekonomian dan distribusi pendapatan masyarakat Indonesia. Indikator ekonomi yang dianalisis adalah output, ketenagakerjaan, PDB, ekspor dan impor. Data yang digunakan dalam penelitian ini adalah data Sistem Neraca Sosial Ekonomi tahun 2008 sebagai data SNSE terbaru yang diterbitkan oleh Badan Pusat Statistik. Peran agroindustri hulu dan hilir ini akan dianalisis menggunakan analisis pengganda neraca. Dalam perekonomian nasional, agroindustri hilir lebih berperan dalam penciptaan output, nilai tambah dan impor. Sementara agroindustri hulu lebih berperan dalam penciptaan, PDB dan ekspor. Dari sisi distribusi pendapatan masyarakat, agroindustri hilir menciptakan distribusi pendapatan yang lebih merata baik bagi rumah tangga pertanian maupun non pertanian.Kata kunci: agroindustri, PDB, distribusi pendapatan, SNSE